Pemanfaatan Media Kantong Bilangan dalam Pembelajaran untuk Meningkatkan Pemahaman Operasi Hitung Siswa Kelas III di SDN Sebaung 2 - Dzaky Isyuniandri; Alfiatus Syarofah (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was conducted at SDN Sebaung 2 with the aim of improving third-grade students’ understanding of arithmetic operations through the use of